THE IMPORTANCE OF OCCUPATIONAL HEALTH IN PRESERVING MEDICAL HEALTH - Isakova Mu’azam Tulkinovna; Sotvoldiyev Islomjon Furqatjon o‘g‘li (World Scientific Research Journal, 2025)
Abstract. Occupational health is a critical determinant of medical health, influencing physical, mental, and social well-being in the workplace. This study investigates the role of occupational health in preventing work-related illnesses, reducing healthcare costs, and enhancing productivity. Using statistical data from diverse industries, the research highlights the correlation between occupational health practices and medical health outcomes. The findings emphasize the need for robust occupational health policies to safeguard workers' health and improve public health outcomes.